(untitled) (Proceeding of the International Conference on Arts and Humanities, 2023)
The spread of COVID-19 resulted in the deactivation of formal classes and distance education and learning have been adopted in all forms of education. Institutions start using virtual classrooms which cause significant changes in teaching style as well as in teaching pedagogy. Therefore, different cloud hosting platforms are used for conducting lectures among them Zoom Meet is perceived as the leader which has been used across the globe by all forms of education providers. Although studies revealed that there are several privacy and security issues associated with Zoom meet which may affect the intention to use it for business and education purposes. Therefore, a study is required to understand the perception of teachers who are using this application more extensively as compared to other professionals. The data has been collected through quota sampling through closed-ended questionnaires and SMART-PLS has been incorporated for the analysis of data. The results indicated that university teachers are aware of the privacy and security issues associated with the use of Zoom Meet and hence are willing to change the mode of teaching for upcoming stages and semesters.